Literature review of cancer mortality and incidence among dentists. Issue 7 (25th January 2007) - Simning, Adam; van Wijngaarden, Edwin
Abstract : This review assesses the epidemiological literature describing dentist mortality and cancer incidence risk. In the dental workplace a variety of hazards may have been historically present or currently exist which can impact dentists' long-term health, including their mortality and cancer incidence. The epidemiological literature of dentistry's health outcomes was reviewed with a focus on all cancers combined and cancers of the brain, lung, reproductive organs and skin. Relevant studies were identified using MEDLINE and NIOSHTIC through early 2006 and from references cited in the articles obtained from these databases. Dentist cancer mortality and incidence generally showed a favourable risk pattern for lung cancer and overall cancer occurrence. Nevertheless, several studies reported an increased risk for certain cancers, such as those of the skin and, to a lesser extent, the brain and female breast. These elevated risks may be related to social status or education level, or may alternatively represent the impact of hazards in the workplace. The evidence for an increased mortality or cancer incidence risk among dentists must be interpreted in light of methodological limitations of published studies. Future studies of dentists would benefit from the assessment of specific occupational exposures rather than relying on job title alone.